Analisis Kecukupan Dan Ketersediaan Beras Di Indonesia (1975-2009) - Noviar, Helmi (PASAI, 2013)
This article examines rice economy in Indonesia during 1975-2009, in particular describing sufficient and stock rice stipulation in that period. As a strategic commodity, rice to be crucial element of strategic issues of food security in Indonesia, mainly post-economic crisis period (1997-2009). This paper study shows that during at that time from beginning period in 1975 which Indonesia Government focus on developing agriculture sector for self-sufficient target, in particular rice production target and attainning in 1984. Following that period, domestic rice production fluctuated, mainlyÂ  tends to decreased steadily, in addition to, obtaining sufficient and stock domestic rice, Indonesia rice importation progresively increase, it become significant in post-economic crisis during 2001-2009. The critical condition in rice domestic stock thus 3,9% of rice domestic production was imported to support domestic supply. Hence, rice average production growth should be greater than average consumption growth with the assumption that the constant growth of Indonesian population. One common policy recommendation is to aim for rice production stabilization from supporting input production such as maintanance agricultural infrastructure regularly and also expand research and technology organic-input to get sustainable rice domestic production in the long-run, in addition to, strict land agricultural policy with respect to condensing land conversion as soon as possible should be accomodated as well.